Preparation of aromatic polyimide particles having clear morphology by polymerization of salt monomers. (December 2016) - Shojo, Daisaku; Sugimori, Hidekazu; Yamazaki, Shinichi; Kimura, Kunio
Crystals of salt monomer prepared from aromatic tetracarboxylic acids and aromatic diamines were polymerized at 220°C for 3 h and at 400°C for 3 h under argon flow. Highly crystalline polyimide particles having clear morphology were obtained with good yield. They were lozenge-like crystals, long plate-like crystals, fibrillar crystals, and spherical aggregates of plate-like crystals. The crystals of salt monomer were polymerized in the solid-state with maintaining the morphology, and therefore the morphology of the polyimide particles were the same to that of the crystals of the corresponding salt monomer. Molecular orientation in the lozenge-shaped crystal of poly( p -phenylene pyromelliteimide) was examined by selected area electron diffraction, and the polymer molecules aligned perpendicular to the plate plane which was the direction of the thickness. Obtained particles possessed good thermal stability.